2020
DOI: 10.1007/s40495-020-00231-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in COVID-19: Potential Mechanism of Action Against SARS-CoV-2

Abstract: Purpose of Review The rapid spread of virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has turned out to be a global emergency. Symptoms of this viral infection, coronavirus disease 2019 (COVID-19), include mild infections of the upper respiratory tract, viral pneumonia, respiratory failure, multiple organ failure and death. Till date, no drugs have been discovered to treat COVID-19 patients, and therefore, a considerable amount of interest has been shown in repurposing the existing drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 70 publications
0
93
0
4
Order By: Relevance
“…The antimalaria drugs chloroquine and hydroxychloroquine have been used to treat SARS-CoV-2 infection despite their potential adverse effects 175 , 176 . The two main mechanisms of action of hydroxychloroquine are believed to be via its restriction of viral spike protein cleavage at the ACE2 binding site, and its anti-inflammatory and immunomodulatory properties 177 . Hydroxychloroquine also has glucose-lowering efficacy by increasing insulin sensitivity and improving pancreatic β-cell function 178 , which has enabled hydroxychloroquine to be prescribed as an antidiabetic medication in some countries 179 .…”
Section: Covid-19 Treatments and Metabolismmentioning
confidence: 99%
“…The antimalaria drugs chloroquine and hydroxychloroquine have been used to treat SARS-CoV-2 infection despite their potential adverse effects 175 , 176 . The two main mechanisms of action of hydroxychloroquine are believed to be via its restriction of viral spike protein cleavage at the ACE2 binding site, and its anti-inflammatory and immunomodulatory properties 177 . Hydroxychloroquine also has glucose-lowering efficacy by increasing insulin sensitivity and improving pancreatic β-cell function 178 , which has enabled hydroxychloroquine to be prescribed as an antidiabetic medication in some countries 179 .…”
Section: Covid-19 Treatments and Metabolismmentioning
confidence: 99%
“…It contains a single strand of a positive-sense RNA genome with 29,903 base pairs [ 61 ]. The viral RNA is enclosed in an enveloped structure and when viewed under an electron microscope, appears as a crown-like structure due to the incorporation of structural spike proteins on its outer surface that facilitates its entry, proliferation, and infectivity in host cells via ACE2 receptors [ 62 , 63 ]. The ACE2 receptors are expressed in epithelial cells of the kidney, heart lungs, and blood vessel endothelial cells.…”
Section: Deciphering the Link Between Sars-cov-2 Proteins And Jak/stamentioning
confidence: 99%
“…The action of CQ and HCQ may be different depending on the type of microorganisms, but it is shown that it targets the interaction between the SARS-CoV and its receptor by hampering the glycosylation of its cellular receptors blocking the SARS-CoV infections [ 125 ]. Besides, CQ/HCQ blocks the sialic acid receptors, thus preventing the entry of SARS-CoV-2 into the upper respiratory tract [ 126 ]. Furthermore, CQ has an immunomodulatory ability on activated immune cells [ 11 , 127 ].…”
Section: Chloroquine/hydroxychloroquine Azithromycin and Coronavirumentioning
confidence: 99%